2018
DOI: 10.4269/ajtmh.18-0143
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe Drinking Water Is Associated with Environmental Enteric Dysfunction and Poor Growth Outcomes in Young Children in Rural Southwestern Uganda

Abstract: Abstract.Environmental enteric dysfunction (EED), a subclinical disorder of the small intestine, and poor growth are associated with living in poor water, sanitation, and hygiene (WASH) conditions, but specific risk factors remain unclear. Nested within a birth cohort study, this study investigates relationships among water quality, EED, and growth in 385 children living in southwestern Uganda. Water quality was assessed using a portable water quality test when children were 6 months, and safe water was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…This study found that within-country changes in stunting risk were associated with improvements in household access to improved sanitation facilities and improved drinking water sources and increased coverage of child immunization, which is consistent with findings from other trend analysis studies [17,18,19,20,22,25]. These findings are supported by the growing body of literature indicating that enteric dysfunction, resulting from poor environmental conditions (water, sanitation, and hygiene), is among the most important factors for the high childhood stunting burden in low-income settings [4,34,35].…”
Section: Discussionsupporting
confidence: 89%
“…This study found that within-country changes in stunting risk were associated with improvements in household access to improved sanitation facilities and improved drinking water sources and increased coverage of child immunization, which is consistent with findings from other trend analysis studies [17,18,19,20,22,25]. These findings are supported by the growing body of literature indicating that enteric dysfunction, resulting from poor environmental conditions (water, sanitation, and hygiene), is among the most important factors for the high childhood stunting burden in low-income settings [4,34,35].…”
Section: Discussionsupporting
confidence: 89%
“…Two studies, each using one or the other putative biomarkers of environmental enteric dysfunction, show convergent findings related to exposure to safer or less-safe household water. With respect to linear growth, the study in Timor-Leste 61 did not report on growth, and in Uganda, 62 the additional growth was not of a magnitude to alter the stunting rates in the community.…”
Section: Emerging Insightsmentioning
confidence: 96%
“…Although small-scale livestock production presents an opportunity for increased ASF production/consumption to halt child undernutrition in LMIC (27,28), a 2018 systematic review revealed no congruent relationship between ASF consumption and the alleviation of common undernutrition outcomes, including stunting (29). Furthermore, although many observational studies significantly associate improved family-level water, sanitation, and hygiene (WaSH) with improved child linear growth and lessened burden of environmental enteric dysfunction (EED), a key mediator of growth faltering (30)(31)(32), these significant effects did not persist in landmark randomized controlled trials (WASH-Benefits Bangladesh & Kenya, SHINE) (33)(34)(35)(36). Researchers suggested that unmeasured household risk factors could have confounded the beneficial effect of WaSH interventions, and called for a "transformative WaSH" approach to curtail fecal contamination at the household level in future research (33).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although many observational studies significantly associate improved family-level water, sanitation, and hygiene (WaSH) with improved child linear growth and lessened burden of environmental enteric dysfunction (EED), a key mediator of growth faltering ( 30 32 ), these significant effects did not persist in landmark randomized controlled trials (WASH-Benefits Bangladesh & Kenya, SHINE) ( 33 36 ). Researchers suggested that unmeasured household risk factors could have confounded the beneficial effect of WaSH interventions, and called for a “transformative WaSH” approach to curtail fecal contamination at the household level in future research ( 33 ).…”
Section: Introductionmentioning
confidence: 99%